Poetry beyond Illocution - Davey, Frank (Studies in Canadian Literature / Études en littérature canadienne, 2016)
Visual and conceptual poetry became significant practices in Canada in the late 1950s and 1960s as part of a dissatisfaction with what Antony Easthope in 1986 would call a moribund “bourgeois poetic discourse,” “the poetry of the ‘single voice.’” The latter, however, would continue to survive in school anthologies and arts council policies as a protected form, while the new non-discursive poetries found most of their audiences in art galleries, libraries, music clubs, on the internet, and as often through international presentation as Canadian. The result has been a rich accumulation of visual and conceptual poetry, with its own major figures, that is little understood or studied nationally and often better known and appreciated outside of Canada than within.